Peran Guru Pendidikan Agama Islam dalam Membina Akhlakul Karimah Peserta Didik di SD Swasta Islam Terpadu Cendekia Kecamatan Medan Helvetia - Ginting, Aisyah Mutiara Ramadhani; Amin, Nazrial; Tambunan, Nurhalima (Islamic Education, 2026)
This study aims to analyze the role and strategies of Islamic Religious Education (IRE) teachers in fostering students’ noble character (akhlakul karimah) through Islamic communication culture at SDIT Cendekia, Padang Pariaman, West Sumatra, Indonesia. Previous studies have generally discussed character education in schools; however, limited research specifically examines how Islamic communication culture is integrated into daily learning interactions and school activities as a strategy for strengthening students’ moral character. This study employed a qualitative research method using observation, in-depth interviews, and documentation techniques. The findings indicate that IRE teachers play important roles as educators, facilitators, counselors, and role models in developing students’ character. The dominant forms of Islamic communication identified in this study include polite verbal interaction, greeting habits (salam culture), persuasive advice, exemplary speech, and personal guidance based on Islamic values. These strategies were implemented through value internalization, uswah hasanah (exemplary behavior), habituation of positive actions, and contextual learning integrated into school culture. The results also show that consistent Islamic communication practices contribute to improving students’ discipline, respect, honesty, and social responsibility. This study implies that strengthening Islamic communication culture can serve as an effective approach for character education in elementary schools and contributes to the development of Islamic-based pedagogical practices in character formation.